Media organisations in society - Curran, James. editor (London Arnold, 2000)
Here is a widescreen approach to the study of media organisations in society. It provides an in-depth understanding of media industries and the processes of cultural production by combining a survey of current research with original case studies. It studies the media as an industry, through critical studies of the Internet, the global standardisation of the mega-musical, the deregulation of television, and alternative media. It views the media as a battlefield, by looking at Amnesty's inspired international campaign against the killing of street children in Brazil, a successful opposition to privatisation, and the rise of Marxism Today. The media are investigated as a cultural product by assessing the processes which determine which books are reviewed and by whom, the elite male tastes which privilege the development of certain forms of popular music, and the way in which public responses to the media are affected by a 'culture of belief.'

For students and researchers investigating media industries and cultural products, this is a unique introduction to current thinking to one of the liveliest areas of research and debate within both media and cultural studies.
Includes bibliographical references and index (pages 289-292).
Keywords: Mass media and culture; Organizational behavior; Mass media -- Social aspects